2014
DOI: 10.1017/s1368980014002742
|View full text |Cite
|
Sign up to set email alerts
|

Healthy food access for urban food desert residents: examination of the food environment, food purchasing practices, diet and BMI

Abstract: Objective Provide a richer understanding of food access and purchasing practices among U.S. urban food desert residents and their association with diet and body mass. Design Data on food purchasing practices, dietary intake, height, and weight from the primary food shopper in randomly selected households (n=1372) was collected. Audits of all neighborhood food stores (n=24) and the most-frequented stores outside the neighborhood (n=16) were conducted. Aspects of food access and purchasing practices and relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 43 publications
8
112
2
2
Order By: Relevance
“…This finding is perhaps not surprising in light of other research showing that the majority of people rarely shop at the supermarket closest to their home (1416) . Our analysis also documents the high demand among this cohort for unhealthy foods such as sweets relative to healthy foods such as fruits and vegetables.…”
Section: Discussionsupporting
confidence: 53%
“…This finding is perhaps not surprising in light of other research showing that the majority of people rarely shop at the supermarket closest to their home (1416) . Our analysis also documents the high demand among this cohort for unhealthy foods such as sweets relative to healthy foods such as fruits and vegetables.…”
Section: Discussionsupporting
confidence: 53%
“…Mothers were asked to estimate how much their family spent on groceries and how much (or what proportion) of that was spent on fruits and vegetables per week in the past month (Dubowitz, et al, 2015). The amount spent on all groceries was divided by the amount spent on fruits and vegetables to obtain the percent of grocery dollars spent on fruits and vegetables.…”
Section: Methodsmentioning
confidence: 99%
“…Studies in urban areas in many developed countries have shown that the food environment has been influenced by the modern built environment, making it increasingly easier to access unhealthy food options [4,5]. This characteristic of the urban food environment has also been described as 'food desert', a term used to describe neighborhoods with limited physical and economic access to healthier food options such as fruits, vegetables and other healthy whole foods [6][7][8]. Food deserts, which are often located in poor neighborhoods, are created when supermarkets and other sources of fresh produce are situated, as part of zoning regulations, further away from living areas or require having private transportation to reach [9][10][11].…”
Section: Introductionmentioning
confidence: 99%